Practicality of E-Modules Based on Contextual Teaching and Learning Models on Renewable Energy Material for Phase E Students - Hufri Hufri; Alifa Hanazahra; Hidayati Hidayati; Rahmat Hidayat (Jurnal Penelitian Pembelajaran Fisika, 2025)
This study was driven by the need for teaching materials that aligned with the Merdeka Curriculum, particularly in context-based learning that connected subject matter to real-life situations. However, the limited availability of relevant teaching materials and the inadequate use of technology in the learning process remained obstacles in enhancing students' understanding of renewable energy concepts. Therefore, this study aimed to develop a practical e-module based on a contextual learning model for Phase E students. The e-module development followed the ADDIE model, which consisted of analysis, design, development, implementation, and evaluation stages. The practicality test involved three high school physics teachers using a teacher practicality instrument questionnaire and 69 Phase E students using a student practicality instrument questionnaire. The results indicate that the developed e-module falls into the "highly practical" category, with an average score of 96% from teachers and 82% from students. Based on these findings, it is concluded that the e-module meets practicality standards and is suitable for supporting students' understanding of renewable energy concepts in school learning.